Operating characteristics and performance improvements of a 500 W traveling-wave thermoacoustic electric generator - Wang, Kai (2015)
Traveling-wave thermoacoustic electric generator has drawn increasing attention due to its great prospect in energy conversion. In this work, a traveling-wave thermoacoustic electric generator capable of generating about 500 W electric power is studied numerically and experimentally. The performances and the operating characteristics of the system under different working conditions are tested and analyzed. The maximum electric powers can be obtained with electric load resistance around 100–120 Ω, and the highest thermal-to-electric efficiencies can be achieved at much larger load resistances. The efficiency at low load resistance is relatively small due to the large pressure amplitudes inside the thermoacoustic system, which increases the dissipations. The variation trends of the electric power and the thermal-to-electric efficiency with the load resistance intrinsically result from the changes of the corresponding acoustic impedance of the linear alternators, which determines the output performance of the thermoacoustic engine meanwhile. The distributions of the acoustic power losses are then calculated and firstly illustrated quantitatively. It is shown that the resonator causes most of the acoustic power losses, and the losses in hot heat exchanger, thermal buffer tube, and feedback tube are also significant. The output performance of the system can be improved by increasing the heating temperature and the mean pressure. A maximum electric power of 473.6 W and a highest thermal-to-electric efficiency of 14.5% are achieved experimentally when the mean pressure is 2.48 MPa and the heating temperature is 650 °C. A pair of linear alternators with a larger swept volume and appropriate acoustic impedances is finally designed to couple with the thermoacoustic torus directly. Numerical results show that the maximum electric power can be increased to 718 W and 1005 W when the mean pressures are kept at 2.48 MPa and 3.20 MPa, corresponding to the improvements of 42.6% and 29.4% compared with those of the original system.